Arboles dispersos dentro de cultivos anuales en el municipio de Ilobasco, El Salvador - García, Edwin; Jaime, Manuel; Mejía, Bayron; Guillén, Luis; Harvey, Celia A. (CATIE, Turrialba (Costa Rica), 2015)
3 ilus. 4 tab. 3 ref.